Chronic Lung Diseases and the Risk of Depressive Symptoms Based on the China Health and Retirement Longitudinal Study: A Prospective Cohort Study - Ren, Xueling; Wang, Shengshu; He, Yan; Lian, Junsong; Lu, Qian; Gao, Yanhong; Wang, Yuling (Frontiers in Psychology, 2021)
Chronic lung diseases (CLD) can reduce patients’ quality of life. However, evidence for relationship between CLD and occurrence with depressive symptom remains unclear. This study aims to estimate the associations between CLD and depressive symptoms incidence, using the data from the China Health and Retirement Longitudinal Study (CHARLS). CLD was identified by survey questionnaire and hospitalization. The follow-up survey was conducted in 2018 and depressive symptoms were assessed by the 10-item Center for Epidemiological Studies Depression Scale (CES-D-10). A total of 10,508 participants were studied with the average follow-up period was 3 years. 2,706 patients (25.8%) with newly diagnosed depressive symptoms were identified. The standardized incidence rate of depressive symptoms in baseline population with and without chronic pulmonary disease were 11.9/100 and 8.3/100 person-years respectively. The cox proportional risk model showed that CLD was a significant predictor of depressive symptoms (HR:1.449, 95% CI: 1.235, 1.700) after adjusting for covariates, and the HRs of depressive symptoms were higher in those participants with current smoking (HR:1.761, 95% CI: 1.319, 2.352), men (HR:1.529, 95% CI: 1.236, 1.892), living in rural areas (HR:1.671, 95% CI: 1.229, 2.272), with dyslipidemia (HR:1.896, 95% CI: 1.180, 3.045) and suffering from comorbidity (HR:1.518, 95% CI: 1.104, 2.087) at baseline survey. CLD was independently risk factor of depressive symptoms in China. The mental health of CLD patients deserve more attention.